PERAN PEMERINTAH PROVINSI DALAM MEMBANGUN KERJASAMA ANTAR DAERAH - Arjul, S.IP, M.Si, Muhammad (Pusat Pelatihan dan Pengambangan dan Kajian Desentralisasi dan Otonomi Daerah Lembaga Administrasi Negara, 2010)
Role of Provincial Government in regional collaboration is strategic and appealing to be studied. The issue is relatively new and has not received attention from various stakeholders. In addition, position and authority of Provincial Government to a certain extent is strategic for the success of regional collaboration. Nevertheless empirical pictures indicated that role of Provincial Government was far from expectation, although it was not completely in-exist. Based on cases study of six Province, dynamics of Provincial Government?s roles in regional collaboration can be observed. The study reveals similarities as well as difference of the dynamics in each Province. It is obvious that the dynamics was influenced by condition facing each Provincial Government that posed problems in managing regional collaboration. In the future, role of Provincial Government in regional collaboration need to be strengthened through several model which have been recommended in this study, ranging from simplest model to more strategic one. It is expected that optimization of Provincial Government?s roles in regional collaboration would bring back strategic position of Provincial Government in front of Local Government as stipulated in Law Number 32 Year 2004.